Approximate Homomorphisms and Derivations on Normed Lie Triple Systems. (7th May 2014) - Kim, Hark-Mahn; Lee, Juri
Abstract : We investigate the generalized Hyers-Ulam stability of homomorphisms and derivations on normed Lie triple systems for the following generalized Cauchy-Jensen additive equationr 0 f ( ( s ∑ j = 1 p x j + t ∑ j = 1 d y j ) / r 0 ) = s ∑ j = 1 p ‍ f ( x j ) + t ∑ j = 1 d ‍ f ( y j ), wherer 0, s, and   t are nonzero real numbers. As a results, we generalize some stability results concerning this equation.